Franz Schubert: The Fragmentary Piano Sonatas - Pare, Arabella (Stuttgart Franz Steiner, 2022)
This study of the fragmentary piano sonatas by Franz Schubert, composed between 1815 and 1825, offers an individual analysis of each work, based upon a tripartite approach. It focuses on the aesthetic-philosophical nature of fragmentary works of art, the philological study of the extant manuscripts as well as recorded notational material and musical analyses.This research includes a new perspective of Schubert's commitment to questions of form and compositional renewal and individuality. The engagement with the incomplete, unfinished and fragmentary piano sonatas makes it possible to see the paths towards the later, more well-known compositions. In these works of the early nineteenth century, the working-processes and musical innovations of the composer Franz Schubert are seen as a development of a highly personal stylistic and formal integrity and independence over the course of a productive and innovative decade. (Taken from: https://www.steiner-verlag.de/Franz-Schubert/9783515131698)
Includes bibliographical references and index.
Keywords: Schubert, Franz -- 1797-1828; Sonata; Piano; Musical analysis; Composing; Music philosophy and esthetics